Homeopathic Treatment in Patients with COVID-19: Analysis of Clinical Evolution and Comparison between Cases in 2020 and 2021 - Fujino, Fernanda Maria Simões da Costa; Olandim, Ana Amélia Campos Claro; Coggan, Jennifer Anne; Carvalho Junior, Antonio Deusany de; Bufalo, Adriana de Queiroz Soares; Takeyama, Eduardo Nishimiya; Sant'Ana, Soraya Cristina; Barnabé, Vagner Doja; Benites, Nilson Roberti (Homeopathy, 2022)
Background The manifestations of coronavirus disease 2019 (COVID-19) can result in several prognoses and lead patients to look for appropriate complementary or alternative treatment options according to their personal situation and available health care. Patients with mild symptoms or those who have not yet reached the maximum severity of their condition are those who seek outpatient care, where homeopathic treatment might be considered, given the well documented history of this medical system in several epidemics in the past.Objective The aim of this study was to compare the homeopathic treatment used for symptomatic cases of COVID-19 in March and April 2020 with cases treated in March and April 2021.Method This is a retrospective observational study based on the analysis of the medical records of symptomatic COVID-19 patients treated on an outpatient basis with homeopathy at the Hahnemanniano George Galvão Institute in São Paulo, Brazil. We analyzed 54 cases, divided into two samples (27 cases in each year), similar in relation to age, gender and origin of the patients.Results The development was distinct in the 2 years, with improvement of symptoms after 3 days of the first homeopathic prescription in 2020 whilst in 2021 the improvement occurred from the sixth day onward. The most frequently prescribed homeopathic medicine also differed in the two samples (Antimonium tartaricum in 2020; Arsenicum album in 2021), which indicates the different disease characteristics at these two moments of the epidemic.Conclusion In 2020, the symptomatology of the cases was mainly acute and the main medicine was Antimonium tartaricum. By comparison, in 2021 a greater interference from individuals' previous chronic miasmatic disease may explain the change in the main medicines used that year, with Arsenicum album being the most prescribed in the cases studied.
Keywords: homeopathy; COVID-19; Arsenicum album; Antimonium tartaricum